(untitled) (Research, Society and Development, 2024)
Introduction - Acute Coronary Syndrome (ACS) represents a spectrum of acute cardiovascular conditions, encompassing Acute Myocardial Infarction (AMI) and Unstable Angina (UA). This medical emergency is characterized by the interruption of blood flow to the heart muscle, resulting from a partial or complete obstruction of the coronary artery. Ticagrelor is a P2Y12 inhibitor antiplatelet agent notable for its potency and efficacy in reducing cardiovascular events in patients with ACS. Objectives - This study aims to compile and evaluate current evidence, highlighting the effectiveness and/or superiority of Ticagrelor in relation to other therapeutic approaches. Methods - We carried out an integrative review of specialized literature, following stages of identifying objectives, planning protocol and search strategies on the EMBASE, Cochrane and MEDLINE platforms. Studies that addressed the pharmacological treatment of ACS were included, focusing on the use of Ticagrelor as the main therapeutic resource compared to other P2Y12 inhibitors. After selection and data extraction, 9 studies were analyzed. Results - Studies comparing Ticagrelor with Clopidogrel or Prasugrel in patients with ACS show similar results in the main outcomes, indicating equivalence between these medications. However, nuances in secondary outcomes reveal that Ticagrelor outperforms Clopidogrel in reducing stent thrombosis and cardiovascular death, but carries a greater risk of bleeding, especially in elderly patients. Conclusion - Ticagrelor has similar efficacy to Clopidogrel and Prasugrel in crucial cardiovascular outcomes. However, their in-depth analysis reveals a considerable risk of bleeding, especially in older patients.